Spodoptera frugiperda (Smith, 1797), an unwelcome visitor reaches the Maltese Islands (Lepidoptera: Noctuidae, Xyleninae) - Seguna, Anthony; Catania, Aldo; Borg, John J.; Sammut, Paul (SHILAP Revista de lepidopterología, 2024)
Spodoptera frugiperda (Smith, 1797) is recorded from the Maltese Islands for the first time.